2019
DOI: 10.1002/ijfe.1756
|View full text |Cite
|
Sign up to set email alerts
|

What drives the adoption of mobile payment? A Malaysian perspective

Abstract: The purpose of this study is to examine the antecedents of behavioural intention to adopt mobile payment among working adults in Malaysia. The variables of the unified theory of acceptance and use of technology 2 (UTAUT2) with perceived security were adopted as a theoretical base. The gathered data through a questionnaire were examined by using multiple linear regression (MLR) analysis. The study revealed that performance expectancy, facilitating conditions, hedonic motivation, and perceived security are signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 51 publications
0
36
0
3
Order By: Relevance
“…Given the aim of this systematic review is to propose a conceptual model with UTAUT2; therefore, the ensuing discussion will focus on the perceived security construct. Perceived security is an antecedent that affects the behavioural intention to adopt mobile payment (Moorthy et al, 2019). Findings from the study by (Merhi et al, 2019;Moorthy et al, 2019;Morosan & DeFranco, 2016;Soodan & Rana, 2020;Wu & Lee, 2017) supported the construct of perceived security to have a significant impact on behavioural intention to use e-wallet system.…”
Section: Model Extension To Utaut2mentioning
confidence: 83%
See 1 more Smart Citation
“…Given the aim of this systematic review is to propose a conceptual model with UTAUT2; therefore, the ensuing discussion will focus on the perceived security construct. Perceived security is an antecedent that affects the behavioural intention to adopt mobile payment (Moorthy et al, 2019). Findings from the study by (Merhi et al, 2019;Moorthy et al, 2019;Morosan & DeFranco, 2016;Soodan & Rana, 2020;Wu & Lee, 2017) supported the construct of perceived security to have a significant impact on behavioural intention to use e-wallet system.…”
Section: Model Extension To Utaut2mentioning
confidence: 83%
“…Perceived security is an antecedent that affects the behavioural intention to adopt mobile payment (Moorthy et al, 2019). Findings from the study by (Merhi et al, 2019;Moorthy et al, 2019;Morosan & DeFranco, 2016;Soodan & Rana, 2020;Wu & Lee, 2017) supported the construct of perceived security to have a significant impact on behavioural intention to use e-wallet system. The findings from these studies have revealed the importance of perceived security in influencing consumers' behavioural intention to adopt an e-wallet system.…”
Section: Model Extension To Utaut2mentioning
confidence: 83%
“…The use of Internet-based commerce has rapidly increased due to the recent advancement of mobile technology [1]. This includes the use of smartphones to perform mobile commerce (m-commerce) [2][3][4]. Global m-commerce sales tripled from USD 1 trillion in 2016 to USD 3 trillion in 2020 and are expected to reach USD 3.56 trillion in 2021 [5].…”
Section: Introductionmentioning
confidence: 99%
“…The policy introduced cash handling charges with the goal to decrease the number of cash payments to prevent revenue leakage, improve efficiency, and reduce transaction costs and the risk for robbery. Studies suggest that implementing a similar cash handling fee in Sweden may better reflect the social cost of cash to make the Swedish payment system more efficient by reducing cash transactions (Moorthy et al 2020, Bergman et al 2007, Segendorf and Jansson 2012a, b, Arvidsson et al 2019, while Martin et al (2018) opined that a host of cultural and infrastructural issues have created major difficulties in ebanking implementation in Nigeria.…”
Section: The Impact Of E-banking On Monetary Policymentioning
confidence: 99%